Enhanced tribological performance of tungsten carbide functionalized surfaces via in-situ formation of low-friction tribofilms. (February 2016) - Totolin, Vladimir; Rodríguez Ripoll, Manel; Jech, Martin; Podgornik, Bojan
Abstract: An innovative in-situ method of generating tungsten disulphide (WS2 ) tribofilms was proposed in this study. It was found that the WS2 tribofilms formed via a tribochemical reaction between tungsten carbide particles embedded in a steel surface and an extreme pressure lubricant additive led to low friction and significantly improved anti-wear properties in humid air. The presence of the WS2 tribofilms was detected by X-ray Photoelectron Spectroscopy and their chemical surface composition was discussed. The friction behaviour was influenced by the rate of WS2 tribofilms formation, EP additive concentration and normal load applied. Moreover, it was found that the WS2 tribofilms were crucial for significant reduction in friction and negligible wear of WC-functionalized steel surfaces. Graphical abstract: Highlights: Tungsten carbide functionalized steel surfaces using machine hammer peening. In-situ formation of a WS2 layer at the sliding interface in humid air. Solid lubrication achieved via a cost-effective and robust process.